Frontline immune checkpoint inhibitor-based combination therapy in metastatic renal cell carcinoma patients with poor performance status. (February 2023) - Carril-Ajuria, Lucía; Colomba, Emeline; Romero-Ferreiro, Carmen; Cerbone, Luigi; Ratta, Raffaele; Barthelemy, Philippe; Vindry, Clarisse; Fléchon, Aude; Cherifi, François; Boughalem, Elouen; Linassier, Claude; Fornarini, Giuseppe; et al.
Abstract: Background: Immune checkpoint inhibitor-based combination therapy (ICI-based combination) is a new standard of care for metastatic clear cell renal cell carcinoma (mRCC) in the frontline setting. Patients with poor performance status (PS) (≥2) were excluded from pivotal trials. Hence, the activity and safety of ICI-based combination therapy in this group of patients is still unknown. Methods: We performed a multicentre retrospective study of PS ≥2 mRCC patients who received frontline ICI-based combination, either nivolumab-ipilimumab (NI) or pembrolizumab-axitinib (AP). Patients' characteristics, clinical outcomes, and toxicity were collected. We analysed overall response rate (ORR), median progression-free survival (mPFS), median overall survival (mOS) and grade ≥3 adverse events (G ≥ 3AEs). The association between the predictive biomarker IPI (immune prognostic index) and ORR/PFS/OS was also evaluated. Results: We identified 70 mRCC patients with PS ≥2 treated with ICI-based combination across 14 institutions between October 2017 and December 2021, including 45 and 25 patients were treated with NI and AP, respectively. Median age at diagnosis was 63 years, 51 (73%) were male, only 17 (24%) had prior nephrectomy, 50 (71%) had synchronous metastatic disease at diagnosis, and 16 (23%) had brain metastases. Sixty-one (87%) and 9 (13%) patients had ECOG (Eastern Cooperative Oncology Group) PS 2 and 3, respectively, and 25 (36%) and 45 (64%) patients were intermediate and poor International Metastatic RCC Database Consortium (IMDC) risk, respectively. Among all, 91% were clear cell RCC, 7 patients had sarcomatoid features. At the time of the analysis (median follow-up 11.1 months), 41% patients were dead. Median PFS and mOS in the entire cohort were 5.4 months and 16.0 months, respectively; ORR was 31%. No significant differences in ORR, PFS, OS, or G ≥3AEs were seen between NI and AP. The intermediate and poor IPI groups were significantly associated with reduced ORR and shorter PFS. Conclusion: We report the first cohort of PS ≥2 mRCC patients treated with frontline ICI-based combination therapy. The survival outcomes in our cohort were inferior to that reported in pivotal trials. No significant differences in ORR, PFS, OS or toxicity were seen between NI and AP. Prospective real-world studies are needed to confirm these results. Highlights: First cohort of poor PS mRCC treated with front line ICI-based combination therapy. The survival outcomes were inferior to that reported in pivotal trials. No significant differences in ORR, PFS or OS were seen between NI and AP. Both NI and AP were well tolerated without significant differences between them.